2015
DOI: 10.4236/ijcm.2015.610094
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Gender Difference of Metabolic Syndrome in Hemodialysis?

Abstract: The prevalence of metabolic syndrome is high in hemodialysis. MS is defined by the combination of high blood pressure, dyslipidemia, central obesity and a state of insulin resistance. The aim of this work is to see if there's a difference by gender in the different parameters of metabolic syndrome and in cardiovascular morbidity in our hemodialysis patients. It is a cross-sectional study of 120 patients older than 18 years on hemodialysis. The metabolic syndrome was defined according to the criteria of the Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…It is similar in the studies of Jalalzadeh (p < 0.001) and Radojica (p = 0.04) [7] [15]. However, in Gorsane's study, diabetes was not associated with metabolic syndrome [10].…”
Section: Factors Associated With Metabolic Syndromesupporting
confidence: 81%
See 1 more Smart Citation
“…It is similar in the studies of Jalalzadeh (p < 0.001) and Radojica (p = 0.04) [7] [15]. However, in Gorsane's study, diabetes was not associated with metabolic syndrome [10].…”
Section: Factors Associated With Metabolic Syndromesupporting
confidence: 81%
“…Jalalzadeh observed among hemodialysis patients in Iran in 2011, 28.7% prevalence; Pérez in Spain in 2014, 29% and Maoujoud in Morocco recorded in 2011, 44% [7] [8] [9]. This prevalence within hemodialysis population may reach 70% [10]. Metabolic syndrome triples the risk of developing cardiovascular disease [9] [11], and increases two-fold mortality among hemodialysis patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…Results of current study showed the percentage of males more than females with non-significant difference between sex of patients p>0.05 and shown as in table (1). Results of current study show that the percentage of males with renal failure more than females and reasons of it may be due largely to the daily effort after exposed then women, large number of protein consume by men than women, also muscle mass in men than women leads to increase concentration of creatinine in men [17] . In addition, result of current study were compatible with results conducted by [18] which express the male with renal failure more than to female.…”
Section: Resultsmentioning
confidence: 67%